Studi Perbandingan Hukum Sistem Transaksi Tol Nontunai Nirsentuh di Indonesia - Rahmadhiratri, Nadya; Fuad, Fokky; Suartini, Suartini (Jurnal Bedah Hukum, 2023)
The number of vehicles passing through the toll road is increasing, causing traffic jams on the toll road. In spirit of improving the efficiency and effectiveness of toll roads, it is necessary to develop a technology in cashless payment system with contactless-based technology to support the implementation of payment integration, eliminate congestion, and distribute traffic volume within toll roads. There were many countries that already implemented this contactless cashless toll payment system. The main objective in this journal is to describe the implementation of contactless cashless toll payment system in Taiwan and Turkey, in relation to the plan of implementing multilane free flow system in Indonesia, aiming to gather the information on how the implementation of multilane free flow system could be applied in Indonesia. The research method used in this journal is doctrinal research. However, there are several similarities or even dissimilarities between the implementation of the multilane free flow system in Taiwan, Turkey compared to the implementation plan in indonesia. Therefore, from a legal point of view, a strong legal basis is urgently needed at first, to adapt this payment system in Indonesia.